Anticholinergic and sedative medications and the risk of vertigo or dizziness in the German primary care setting: a matched case‐control study from the CONTENT registry - Phillips, Amanda; Laux, Gunter (Pharmacoepidemiology and drug safety, 2018)
Purpose - To date, there is little information on the utilization of anticholinergic and sedative (AS) medications to vertigo or dizziness (VoD) patients in the German primary care setting.
Gesehen am 21.04.2020